2014
DOI: 10.3389/fphar.2014.00137
|View full text |Cite|
|
Sign up to set email alerts
|

Water hyacinth: a possible alternative rate retarding natural polymer used in sustained release tablet design

Abstract: In recent years natural polymers have been widely used because of their effectiveness and availability over synthetic polymers. In this present investigation matrix tablets of Metformin hydrochloride were formulated using Water hyacinth powder and its rate retardant activity was studied. Tablets were prepared using wet granulation method with 8% starch as granulating agent and 5, 10, 15, 20, 25 and 30% of Water hyacinth powder to the drug. In preformulation study, angle of repose, Carr's Index and Hausner rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…An in vitro dissolution study conducted using simulated intestinal media showed that dissolution time ranged from 1 to 5 min depending on the amount of hyacinth present. Although combining water hyacinth powder (5%) with a drug provided desired release rates, the biocompatibility and any possible adverse effects of the water hyacinth powder were not investigated …”
Section: Controlled Drug Releasementioning
confidence: 99%
See 4 more Smart Citations
“…An in vitro dissolution study conducted using simulated intestinal media showed that dissolution time ranged from 1 to 5 min depending on the amount of hyacinth present. Although combining water hyacinth powder (5%) with a drug provided desired release rates, the biocompatibility and any possible adverse effects of the water hyacinth powder were not investigated …”
Section: Controlled Drug Releasementioning
confidence: 99%
“…Efficiency of the biocomposite to remove reactive dyes from textile wastewater was studied . Surface area of the biocomposite was considerably higher at 173 m/g compared to 133 m 2 /g for the untreated samples. Similarly, micropore volume had increased from 0.0774 to 0.0913 cm 3 /g.…”
Section: Reinforcement For Compositesmentioning
confidence: 99%
See 3 more Smart Citations